2009
DOI: 10.1007/s12149-009-0253-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with myocardial salvage immediately after emergent percutaneous coronary intervention in patients with ST-elevation acute myocardial infarction

Abstract: This study demonstrated that patients with a greater improvement of (99m)Tc tetrofosmin myocardial uptake immediately after PCI had better recovery of left ventricular function and smaller final infarct size. Reperfusion time and TIMI flow grade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In terms of its utility in determining the long-term fate of salvaged myocardial tissue, there has been a recent report of a study of patients with ST-segment elevation acute myocardial infarction, which showed that greatly improved technetium-99m tetrofosmin myocardial uptake immediately after treatment heralded better recovery of left ventricular function and smaller final infarct size (one month after emergent percutaneous coronary intervention). 65…”
Section: Magnetic Resonance Imaging Approachesmentioning
confidence: 99%
“…In terms of its utility in determining the long-term fate of salvaged myocardial tissue, there has been a recent report of a study of patients with ST-segment elevation acute myocardial infarction, which showed that greatly improved technetium-99m tetrofosmin myocardial uptake immediately after treatment heralded better recovery of left ventricular function and smaller final infarct size (one month after emergent percutaneous coronary intervention). 65…”
Section: Magnetic Resonance Imaging Approachesmentioning
confidence: 99%